Cyberbullying and cyber counseling services - Radiani, Widiya Aris; Fadilah, Haris (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Cyberbullying is very important to address because this phenomenon is increasing along with the use of social media, especially among teenagers. Sometimes the perpetrator does not understand that he has committed cyberbullying and the victim does not understand if he has experienced bullying which can have a negative impact on his psychology. Therefore, cyber counseling in the form of group guidance is needed to increase understanding of cyberbullying. This is the purpose of the research. This research is included in quantitative experimental research with a one group pretest-posttest design. Data collection methods used psychological scale measuring instruments, interviews and observations. The data analysis technique used was SPSS 22 with t-test and Nomalized Gain (N-Gain) test. The subjects of this study were ninth grade students at SMP 23 Banjarmasin. The results showed an increase in understanding of cyberbullying (medium and high understanding level categories) with N-Gain values showing changes in values from pretest to posttest (from 17.6 increased in posttest with an average value of 27.7). For hypothesis testing, t count> t table (7.906> 1.812) or sig <0.05, which means that there is an effect on the treatment given, so that understanding of cyber bullying increases after cyber counselling services. This research can be implied in strengthening the digital literacy curriculum, teacher training, and anti-cyberbullying policies in schools.